Characterization of bovine milk production systems in a municipality in the Brazilian semiarid region - Paes, Cristiano da Silva; Góes, Glêidson Bezerra de; Conrado, Jefte Arnon de Almeida (Revista de Ciências Agroveterinárias, 2023)
The realization of diagnoses of agricultural activities becomes essential, especially in those municipalities that depend on the sector to enrich the GDP and generate employment and income, since this collected information directs efficient public policies. The objective was to investigate how the bovine milk production systems in the municipality of Quixeramobim/CE are organized and distributed. A survey was carried out by applying a questionnaire to ranchers during the foot-and-mouth disease vaccination campaign, having quantified some variables, such as: milk production (L/day), total cows (head), lactating cows (head), property area (ha), geographic location in the municipality and some zootechnical indices derived from the relationship of the matrices with the volume of milk produced. It was observed that Quixeramobim produces approximately 151,602 L/day of milk, with a total of 15,694 milked cows (head, with the districts of Damião Carneiro and Encantado being the highest (29,538 L/day) and lowest (5,629 L/day) volumes produced, respectively. It was also noted that the districts of Nenelândia and Encantado were the ones that presented the highest (17%) and lowest (3%) numbers of producers in relation to the total, respectively, of the municipality, and most of them, according to the condition of land use, are owners (43%), and a small part (4%) are considered residents. Quixeramobim has dairy cattle as one of its main activities, which has been characterized by high variability throughout its territory, which is indicative at the time of generation and application of specific public policies, taking into account the specificities of each location.